PENGEMBANGAN INDEKS PENGUNGKAPAN DENGAN MAQASHID SYARIAH DALAM MEMUNCULKAN INDIRECT STAKEHOLDER YANG TERLUPAKAN - Krisno Septyan (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2019)
This research is aims to add of disclosure item based on maqashid shariah ( hifzun Nasb Approach). This reseeach used qualitative method with cristism paradigm based on islam perspective and spiritualism paradigm. Result shows that Islamic bank in Indonesia has more disclose about direct stakeholder than indirect stakeholder. Even that new stakeholder (family) has a little more on disclosure percentage than others stakeholders. Another finding is transfer welfare policy for another stakeholder which should for this new stakeholder